Shock-wave and high-strain-rate phenomena in materials - Meyers, Marc A.; Murr, Lawrence Eugene; Staudhammer, Karl P. (Mechanical engineering (Marcel Dekker, Inc.), 1992)
Includes proceedings of EXPLOMET 90, the International Conference on the Materials Effects of Shock-Wave and High-Strain-Rate Phenomena, held August 1990, in La Jolla, California, which represent a global appraisal of this field.